Home viewing of educational video improves patient understanding of Mohs micrographic surgery. (22nd September 2021) - Mann, J.; Li, L.; Kulakov, E.; Bassett, P.; Birnie, A.
Summary: Background: Educational videos improve patient knowledge of wound care and skin cancer. However, the effect of viewing an educational video at home before undergoing Mohs micrographic surgery (MMS) has not been demonstrated. Aim: To evaluate the use of an educational video to improve patient understanding of MMS. Methods: Patients scheduled to undergo MMS were randomized to receive standard patient education, or standard patient education with an additional video developed by the authors. The educational material was posted to patients along with the details of their MMS appointment. Both groups answered questionnaires to assess their knowledge of MMS, and to measure their anxiety and satisfaction. Results: Patients who watched the educational video scored higher on the knowledge questionnaire than did patients in the control group (0.8, 95% CI 0.3 to 1.4, P < 0.01), but were not statistically less anxious (−0.7, 95% CI −2.6 to 1.3, P = 0.50). Overall, patients undergoing MMS were satisfied. Conclusion: Home viewing of an educational video before MMS can improve patient understanding. Abstract : Our randomized‐controlled study evaluates the use of an educational video to improve patient understanding of Mohs micrographic surgery. Results show improved patient knowledge after home viewing of a short educational video.